Buyer–supplier relationship and optimisation model in a dynamic collaborative network with shortages allowed. Issue 7 (3rd July 2017) - Chen, Liang-Tu
Abstract : To remain competitive, enterprises must build and manage product/service customisation and dynamic collaborative networks to respond to market needs in a flexible manner with competitive price and high product/service quality. This study deals with the emerging research problem of optimally dynamic combined decisions: retail price, stock depletion time/service level (SL) and replenishment schedule/quantity in a decentralised two-echelon perishable product collaborative network comprising a single supplier and a single retailer (buyer) over a finite multi-period planning horizon. Analytical solutions are derived using calculus with dynamic programming under two different trading policies, namely retailer-managed inventory with price-only (RMIPO) mode and vendor-managed inventory with consignment contract (VMICC) mode. In both models, shortages are allowed and are fully backlogged. The validity of the proposed approach is demonstrated using the case of a simple supply chain comprising a regional seafood supplier and a local branch store of a national retail chain. The results show that the VMICC policy yields lower retail price, larger replenishment quantity, higher SL and greater channel-wide profit than the RMIPO policy and achieves a win-win situation for both parties in the supply chain. Additionally, consumers benefit from lower retail price and higher SL in the VMICC policy.